Galactin-3: diagnostic and prognostic value in patients with chronic heart failure - A M Aliyeva; I E Baykova; V A Kislyakov; E T Gasanova; I I Almazova; T V Pinchuk; Yu N Fedulayev; I V Zhbanov; V A Perevertov; I V Kovtyukh; I G Nikitin; E V Reznik (Терапевтический архив, 2019)
Now there is a relevant development of the new biomarkers capable to serve as the instrument of early diagnostics of a disease for the purpose of selection of a pharmacotherapy and further monitoring of its efficiency. Galektin-3 is the atypical representative of the family of galektin. Its participation in fibrosis, remodeling of heart, the immunologic answer and inflammatory reactions are shown. Prognostic value is discussed and diagnostic opportunities of Galektin-3 at CHF are widely studied and take root into clinical practice. Now a great deal of research devoted to the studying of Galektin-3, possibilities of its use as a biomarker at diagnostics, forecasting of outcomes and the choice of therapeutic strategy at other cardiovascular diseases has been conducted.